2015
DOI: 10.1371/journal.pone.0120118
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 Regulates the Proliferation of Radial Glial Cells in the Developing Xenopus Tectum

Abstract: In the developing central nervous system (CNS), progenitor cells differentiate into progeny to form functional neural circuits. Radial glial cells (RGs) are a transient progenitor cell type that is present during neurogenesis. It is thought that a combination of neural trophic factors, neurotransmitters and electrical activity regulates the proliferation and differentiation of RGs. However, it is less clear how epigenetic modulation changes RG proliferation. We sought to explore the effect of histone deacetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 56 publications
1
43
0
Order By: Relevance
“…Comparatively, the current results in the telencephalon of Xenopus with previous studies in other brain regions, such as the optic tectum, the number of dividing precursor cells along the tectal ventricular layer decreased through development from stage 46 to stage 49 (Tao et al, 2015), which is largely similar to the observations in the pallium, specially in the pallium versus SPa. These results concur with similar data reported in the spinal cord (Thuret et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Comparatively, the current results in the telencephalon of Xenopus with previous studies in other brain regions, such as the optic tectum, the number of dividing precursor cells along the tectal ventricular layer decreased through development from stage 46 to stage 49 (Tao et al, 2015), which is largely similar to the observations in the pallium, specially in the pallium versus SPa. These results concur with similar data reported in the spinal cord (Thuret et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Although general patterns of cell proliferation in the anuran brain have been studied (Wullimann et al, 2005; Chapman et al, 2006; Raucci et al, 2006; Simmons et al, 2006; Coen et al, 2007; Denver et al, 2009; Tao et al, 2015; Thuret et al, 2015), no detailed analysis of the pallium has been performed. We have selected some markers of the main proliferative events described in other vertebrates (PH3, PCNA and BrdU assays), which had previously been successfully used in Xenopus (D’Amico et al, 2011, 2013; Auger et al, 2012; McKeown et al, 2013) and allowed us to conduct birth-dating and mitotic rate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Class I histone deacetylases (HDACs) – in particular, the homologous enzymes Hdac1 and Hdac2 – are emerging players in nervous system development and function (Castelo-Branco et al, 2014; Hagelkruys et al, 2014; Montgomery et al, 2009; Tao et al, 2015; Wang et al, 2010; Ye et al, 2009). The significance of HDACs became evident in recent studies showing that both histone acetylation and deacetylation act during neurogenesis in a highly context-dependent manner (MacDonald and Roskams, 2008; Montgomery et al, 2009; Yao and Jin, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The HDAC1 orthologues in homo sapiens and Xenopus laevis share 90.46% protein sequence homology (Tao et al, ). We found that HDAC1 was ubiquitously expressed throughout the cell layer and predominantly localized within the cell nuclei of the Xenopus tectum at stage 47 [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, acute overexpression of HDAC1 regulates extinction of fear memory in the adult brain (Bahari‐Javan et al, ) and inhibitory synaptic transmission in cultured hippocampal slices (Hanson et al, ). Although HDAC1 has been shown to play a role in neural proliferation/differentiation (Yamaguchi et al, ; Cunliffe and Casaccia‐Bonnefil, ; Brunmeir et al, ; Ye et al, ; Dovey et al, ; Conway et al, ; Jacob et al, ; Tao et al, ), learning and memory (Bahari‐Javan et al, ), neuronal survival and death (Kim et al, ; Kim et al, ; Bardai et al, ) and neurological diseases (Abel and Zukin, ; Chen et al, ; Jia et al, ; Rudenko and Tsai, ), there is limited evidence for HDAC1 in neuronal dendritic growth and structural plasticity. Recent work has shown that visual avoidance behavior can be used to measure the function of the visual circuit (Dong et al, ; Shen et al, ); however, the role of HDAC1 in the behavior and underlying cellular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%